Study on the sensory and nutritional properties of developed food products by the incorporation of Quinoa and Ragi flour (International Journal of Food and Nutritional Sciences, 2022)
In the present study, the quinoa bar was prepared by combining different proportions of quinoa and ragi flour, as well as various traditional products prepared by incorporating quinoa using various cooking techniques, including baking (cookies), roasting (laddu, khakhara), and frying (mathari). For the various formulations, the quinoa and ragi flour levels varied from 0 to 10, 20, 30, and 40 % for T0, T1, T2, T3, and T4, respectively. In terms of sensory quality, the ratios of 30 % quinoa, 30 % ragi, and 40 % wheat flour or refined flour in khakhara, mathari, and laddu, and 20 % quinoa, 20 % ragi, and 60 % wheat flour in cookies were determined to be acceptable. The sensory features and nutritional content of the manufactured items were examined. It was discovered that quinoa-ragi based products were an excellent source of protein ash, crude fibre, and iron. Thus, ragi and quinoa flour may be effectively exploited as a functional component in the preparation of nutritional quinoa-based food products.